The expression of meaning as a logical approach in the case of semantic study - Yaacob, Solehah@Nik Najah Fadilah (IIUM Press, 2011)
According to Jurjani, the relationship between syntax and semantics has not been effectively clarified within the framework of traditional Arabic grammatical theory. In his commentary (see Jurjani, Dalā’il al-I’jāz, 1960, p.66-67) he differentiated between ‘meaning’ and ‘form’ in a sentence. This concept is presented not to linguists but theologians (Mu`tazilah) in impressing on them the need to study not only theology but also grammar and literary theory in order to improve their understanding of the inimitability of the Qur’an. In this case, the concept of nazm combines three aspects which are: 1) lafz hāmil, 2) makna bihi qāim and 3) rabat lahuma nāzim. This contribution showed the intellectual capacity of Jurjani, particularly when he argued that one could not have the right meaning if not constructed with lafz and rabat in order to produce a nazm. In other words, for those who have reached the level of eloquence (fasāhah) will not produce a coherent sentence unless they combine the group of words according to their concurrence followed by the meaning. Starting from here, we know that he focused more on the system of nazm and movement among the words after their combination. This means that eloquence does not depend on single words and producing coherent meaning. His major contribution to the discussion of unimitability (i’jāz) of the Qur’an was on ma`ānī (meanings) and lafz (expression). Both concepts have been subject to debate between logicians and grammarians. According to the logicians, meanings were logical ideas signified by expressions, while the grammarians concentrated on the functions of the words.